2015
DOI: 10.1152/physiolgenomics.00006.2015
|View full text |Cite
|
Sign up to set email alerts
|

Extreme obesity is associated with variation in genes related to the circadian rhythm of food intake and hypothalamic signaling

Abstract: The hypothalamus is important for regulation of energy intake. Mutations in genes involved in the function of the hypothalamus can lead to early-onset severe obesity. To look further into this, we have followed a strategy that allowed us to identify rare and common gene variants as candidates for the background of extreme obesity from a relatively small cohort. For that we focused on subjects with a well-selected phenotype and on a defined gene set and used a rich source of genetic data with stringent cut-off … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…In Human study links the polymorphism in NUCB2 gene to the risk of obesity (34). Further clarifying the role of NUCB2/nesfain-1 in the PVN regulation of metabolic and fluid balance could provide a novel therapeutic target for treating obesity, hypertension, and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In Human study links the polymorphism in NUCB2 gene to the risk of obesity (34). Further clarifying the role of NUCB2/nesfain-1 in the PVN regulation of metabolic and fluid balance could provide a novel therapeutic target for treating obesity, hypertension, and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been associated with the percentage of visceral and body fat, BMI, hip circumference, and glucose levels. Several studies have reported that mutations in the genes encoding leptin (LEP) and its receptor (LEPR) have been associated with hyperphagia and morbid obesity [27, 28]. Jeon et al show that higher copy numbers of the LEPR exon 2 may contribute to higher transcriptional activity of LEPROT by a gene dosage effect, which may be accordingly responsible for LEPR downregulation in T2D patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may have contributed to these inconsistencies in the current literature. Most of the studies observing lower binding in obesity compared extremely obese subjects (BMI > 40) with normal weight subjects, and these findings may not generalize to other BMI ranges, especially in light of evidence that extreme obesity may reflect a state of aberrance distinct from other BMI categories (28). Additionally, the sample sizes of most PET studies were small, with most having less than two dozen subjects.…”
Section: Introductionmentioning
confidence: 98%